Polish poster in public health campaigns in the years 1945-1956 - Duber, Paweł; Chmura, Robert; Krajewski-Siuda, Krzysztof (Polish Journal of Public Health, 2010)
Introduction. The poster as a tool of commercial campaigns appeared in 1870. However, as early as the end of the 19th century it becomes an element of health campaigns. Aim. The aim of the present research was to demonstrate the specificity and use of the poster in public health campaigns in the Stalinist period (1945-1956) in Poland. Material and methods. The analysis was based on the materials from the collection of the Jagiellonian Library in Kraków and the Internet sources. Conclusions. The posters used in health campaigns focused on the problems of communicable diseases (mostly tuberculosis) and alcoholism. The mainstream of the poster art was socialist realism. The posters from that period were treated as a tool of the socialist propaganda. The health poster of the Stalin era reveals complicated connections between the sphere of public health and the phenomena of the political stage.